Hybrid photonic device based on Graphene Oxide (GO) doped P3HT-PCBM/p-Silicon for photonic applications - Demirezen, S.; Dere, A.; Cetinkaya, H. G.; Al-Sehemi, A. G.; Al-Ghamdi, A. A.; Yakuphanoğlu, Fahrettin (Iop Publishing Ltd, 2023)
Graphene oxide (GO) doped poly(3-hexylthiophene):[6,6]-phenyl C61 butyric acid methyl ester (P3HT:PCBM) interlayered Al/p-Si Schottky barrier diodes (SBDs) were manufactured by spin coating technique and investigated for the effects of GO concentration on electrical and photodiode parameters. The current-voltage (I-V), measurements for the different mass ratios of GO:P3HT:PCBM (0:1:1(S1), 0.5:1:1(S2) and 2:1:1(S3)) used diodes allowed the determination of key electrical parameters, including ideality factor (n), barrier height (Phi(B)), series resistance (R-s), shunt resistance (R-sh), interface states density (N-ss) and optical sensing behaviors in dark and different illumination levels (10, 30, 60, 80 and 100 mW cm(-2)). The rectification ratio (RR) was found to be in the order of 10(4). The trends obtained for the n, Phi(B), R-s/R-sh and N-ss show that these are influenced by the contribution of the GO. Observed increasing behavior of reverse current with increasing illumination shows that this SBDs can be use as photo-diodes/sensors/detectors. On the other hand, it was observed that the linear dynamic range (LDR), which is important parameter for image sensors, increased (6.86, 16.95 and 26.98 for S1, S2 and S3, respectively) with increasing GO contribution. In addition, to investigate and compare in more detail, capacitance-voltage (C-V) and conductance-voltage (G-V) measurements used for the determination of diffusion potential (V-D), concentration of dopant acceptor atoms (N-A), Fermi energy level (E-F), depletion layer width (W-D) for low frequency (1 kHz) and high frequency (1 MHz). The measured capacitance values showed a high value at the low frequency in comparison with the high frequency. This behavior explained on the basis of N-ss. The findings suggest that the prepared diodes has the potential to serve as a photo-diodes/sensors/detectors for optical sensing applications.
Keywords: P3HT:PCBM/p-Si photodiodes; comparison of the electrical and photo-response characteristics; Al/GO:P3HT:PCBM/p-Si photodiodes